The Potential Development of Mathematics Education to Support the Achievement of Sustainable Development Goals (SDGs) in the Digital Era - Nurwahid, Mohammad; Ashar, Sofia; Rosmaiyadi, Rosmaiyadi (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3810, 2025)
This study explores the developmental potential of mathematics education in supporting the Sustainable Development Goals (SDGs) in the digital era through an enhanced narrative review approach. To strengthen methodological rigor, the review adopted a structured four-phase procedure inspired by narrative synthesis and qualitative evidence integration. The Identification phase involved a comprehensive search across Scopus, ERIC, SpringerLink, and Taylor & Francis Online focusing on recent developments from 2024–2025 a period marked by rapid global expansion of SDG-oriented and technology-enhanced mathematics education research. The Screening and Eligibility phase applied explicit inclusion criteria to refine the corpus to 33 high-quality, thematically relevant studies. The Thematic Analysis phase employed qualitative coding to derive recurring concepts related to curriculum, digital transformation, and teacher competencies. Finally, the Synthesis phase integrated these themes into a conceptual framework describing emerging potentials of mathematics education to advance SDGs. Three central potentials were identified: (1) Curricular Innovation and Localization, emphasizing sustainability based contextualization; (2) Digital Empowerment and Technological Integration, highlighting AI-supported learning and data-driven modelling; and (3) Capacity Building and Collaborative Policy Action, stressing the importance of teacher development and cross-sector partnerships. The findings demonstrate that mathematics education, when aligned with sustainability and digital transformation, functions as a transformative driver that nurtures sustainable mindsets, digital literacy, and ethical awareness essential for SDG achievement.